Knowledge Management, Information Technology and Learning in Construction Projects - Jäväjä, Päivi (My University, 2008)
ICT (Information and Communication Technology) usage in construction is limited when compared with other industries. This may be due to the unique characteristics of the construction industry and the tendency for late take-up of ICT solutions. The amount and diversity of information created and referenced during a typical construction project is considerable. Most people working in the construction business have been involved in projects where costs have enormously exceeded the budget, where timetables have caused problems, and where the end results have been useless or even unhealthy for people. The KM (Knowledge Management) in construction projects fails, and there is no commitment to improve the process even if productivity in the industry is very low compared to other industries. Construction professionals work in complex and heterogeneous networks of human beings and various artefacts. Productive participation in knowledge-intensive work requires that both individual professionals and their communities and organisations continuously transform their practices, develop new competencies, advance their knowledge and understanding, as well as produce innovations and create new knowledge. This present thesis is a case study conducted within the Prolab project in Vaasa University. This study deals with the issues and problems of knowledge management in construction projects. The focus is in construction ICT and solutions that have emerged in this field. There are five published articles that relate to these themes. The empirical part for this study comes from the Prolab project interviews in five demanding public construction projects. The informants were project stakeholders; end-users of the buildings, such as nurses and teachers; architects and special designers; as well as project managers and contractors. My conclusions are that the knowledge processing tools are in use but they are not used in as centralized or intelligent way as they could be. It seems that the solutions are not interoperable because of technical problems. In addition, I found problems related to inefficient information flow, lack of communication and project participants not being ready to utilize the modern technologies, as well as to the lack of centralised KM strategy. In order to improve the process, construction companies must integrate learning with dayto-day work processes in such a way that they not only share knowledge but also provide access to knowledge at any level. The knowledge portal systems that include BIM (Building Information Modelling) operations and perceive user and business requirements are one way to innovative project management systems. Continual discussion between customer and the application provider is necessary for the best results.
Keywords: Knowledge management; learning; e-learning; construction project; construction ICT; fi=Tietotekniikka (KTM)|en=Computer Science|